1979
DOI: 10.1002/jez.1402070305
|View full text |Cite
|
Sign up to set email alerts
|

The progesterone receptor‐like properies of Xenopus laevis oocyte melanosomes are probably due to eumelanin

Abstract: The binding of progesterone to t h e melanosomes of t h e Xenopus laeuis oocyte was examined. Based upon the similarities between the eumelanin complex, which is prepared by stripping melanosomes of their proteins, and synthetic melanin in regard to their association with progesterone and other steroids, the data strongly suggest that eumelanin rather than a protein is responsible for the receptor-like properties of the melanosomes.It is generally assumed that steroid-responsive cells contain a receptor that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We have shown the Na + ,K + ‐ATPase is predominantly localized over the animal hemisphere. Similarly, the following are also mainly expressed in the animal hemisphere: GABA receptor (Chapell et al, 1998), muscarinic acetylcholine receptors, thyrotropin releasing hormone receptors (Kusano et al, 1982; Oron et al, 1988), progesterone receptors (Coffman et al, 1979; Smith, 1989), reduced folate carrier (hRFC) (Subramanian et al, 2001), endogenous G‐proteins and other signaling components (Oron et al, 1988), Ca 2+ ‐sensitive Cl‐channels (Robinson, 1979), U‐cadherin (Muller et al, 1992), and β1‐integrin (Muller et al, 1993). Kir (2.1) potassium channels (Wild and Paysan, 2002), apical amiloride‐sensitive epithelial Na + channels (Mastroberardino et al, 1998), and nicotinic acetylcholine receptors (Barnard et al, 1992), on the other hand, are targeted to the vegetal hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown the Na + ,K + ‐ATPase is predominantly localized over the animal hemisphere. Similarly, the following are also mainly expressed in the animal hemisphere: GABA receptor (Chapell et al, 1998), muscarinic acetylcholine receptors, thyrotropin releasing hormone receptors (Kusano et al, 1982; Oron et al, 1988), progesterone receptors (Coffman et al, 1979; Smith, 1989), reduced folate carrier (hRFC) (Subramanian et al, 2001), endogenous G‐proteins and other signaling components (Oron et al, 1988), Ca 2+ ‐sensitive Cl‐channels (Robinson, 1979), U‐cadherin (Muller et al, 1992), and β1‐integrin (Muller et al, 1993). Kir (2.1) potassium channels (Wild and Paysan, 2002), apical amiloride‐sensitive epithelial Na + channels (Mastroberardino et al, 1998), and nicotinic acetylcholine receptors (Barnard et al, 1992), on the other hand, are targeted to the vegetal hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…In membrane samples prepared from pigmented frogs, the melanin contamination could not be totally eliminated. Because progesterone can bind to melanin [14], Scatchard analyses of the samples prepared from albino frog ovaries were performed to determine whether receptor binding activity could also be found in melanin-free preparations. Similar results were obtained in these preparations (Table 1), indicating that melanin did not interfere with the progesterone binding activity in the regular samples.…”
Section: Resultsmentioning
confidence: 99%
“…This is relevant to note, since it has been reported that progesterone can bind to melanin [14]. It is also important to mention that intracellular (cytosolic and organelle) binding sites for progesterone in the amphibian oocyte have been previously ruled out [8,18].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation